Dukungan Keluarga pada Orang dengan Gangguan Jiwa di Masa Pandemi Covid-19 - Eko Mulyadi; Yulia Wardita; Hadina Eka Camalia; Abd Wahid; Dwi Rahayu Wulandari (Wiraraja Medika : Jurnal Kesehatan, 2021)
Patients mental disorders still are a serious problem during the COVID-19 pandemic, because patients mental disorder still roaming around in the street without wearing masks, many patients with mental disorders are confined to their homes because family a worried about the patient's condition, which is suspected to be able to disrupt the comfort activities of local residents, this illustrates the lack of family support for patients mental disorder. The aims of this study to describe family support for mental disorder patients, study was conducted in the village of Kaduara Barat, Pamekasan, with 25 family of mental patients as a sample, the research variables were family support, the research instrument used questionnaires and descriptive analysis. Characteristics of Respondents are mostly 17-25 years old the category of teenagers and adults, more than half that respondents are women with unmarried status, all respondents are Muslim with jobs as entrepreneurs. almost all respondents have a family with a mental disorder, and having a relationship with the patient as a cousin. The results showed that more than the family had provided positive support. positive cognitive support is provided by families with the age range of 17 to 25 years, while on affective support, there are still many who support negatively, almost girls, with 17 to 25 years old, with a relationship as brother and cousin with unmarried status, working as an entrepreneur and having a family history of mental disorders.